Social contexts of early education, and reconceptualizing play (II) - Reifel, Robert Stuart; Brown, Mac H. (Amsterdam ; Oxford : Elsevier JAI, 2004)
This volume revisits a number of themes that have appeared in earlier "Advances" publications, including "Social Contexts of Early Development" and "Education and Reconceptualizing Play". New social contexts for early education and care often require that we aim our inquiry at social conditions that have not existed in the past, as well as elaborating long-standing concerns. Studies of some of the social contexts of early education point to how many of the needs of the field are unique, depending on where and when we do our work, and with whom we work. "Reconceptualizing Play" points to the multiple perspectives that teachers, researchers, parents, and children bring to our understanding of play. Culture, policy, belief, and values prove to be worthy lenses for enhancing our developmental views of childhood play and practice. Our hope is that others will build on some of these reconceptualizations, to assist teachers and families to improve the lives of children in their programs.
Introduction / Stuart Reife -- Young children's ideas about poverty: gender, race, socioeconomic status, and setting differences / Judith A. Chafel, Carin Neitzel -- Blocks, building and mathematics: influences of task format and gender of play partners among preschoolers / Jody L. Eberly, Susan L. Golbeck -- Beyond quality, advancing social justice and equity: interdisciplinary explorations of working for equity and social justice in early childhood education / Sheralyn Campbell, Glenda MacNaughton, Jane Page, Sharne Rolfe -- Between a rock and a hard place: teachers' experiences in meeting the Abbott mandate / Debra J. Ackerman -- Lessons from home: a look at culture and development / Irma Cantú Woods -- Beyond fun and games towards a meaningful theory of play: can a hermeneutic perspective contribute? / Karen VanderVen -- From context to texts: DAP, hermeneutics, and reading classroom play / Stuart Reifel, Priscilla Hoke, Dianne Pape, Debora Wisneski -- Reconceptualizing rough and tumble play: ban the banning / Nancy K. Freeman, Mac H. Brown -- War play, aggression and peer culture: a review of the research examining the relationship between war play and aggression / Heidi L. Malloy, Paula McMurray-Schwarz -- Los padres y los maestros: perspectives of play among bilingual stakeholders in public schools / Mari Riojas-Cortez, Belinda Bustos Flores.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Early childhood education; Child care; Play; Pre-school & kindergarten; Child & developmental psychology; Education -- Preschool & Kindergarten; Family & Relationships -- Parenting -- Child Rearing